IDEOLOGI DALAM TERJEMAHAN ALQURAN PEREMPUAN BAHASA INGGRIS - Zunaidi Nur (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2018)
For centuries, the Al-Qur'an translator was dominated by men while women's participation in the translation of the Qur'an was still very minimal. This means, only the experience of men involved in the process of translating the Qur'an finally the Qur'an is only understood according to men's views. Therefore, this article aims to look at the translation of the female Qur'an. Does the involvement of women in the translation of the Qur'an necessitate translations that uphold the principles of egalitarianism as the ideology of feminism or only continue the translation of the Qur'an written by men who support patriarchal ideology? By using a critical linguistic approach that aims to find out the ideology in the translation of the Qur'an through language analysis, the authors conclude that some translations of women's Qur'an affirm the translation of the male Al-Qur'an in favor of the patriarchal ideology reflected in the use of vocabulary protector, managers, have charge of, overseer, beat and hit. While others bring feminism ideology that upholds the principles of egalitarianism and justice which are reflected in the use of the word to support, supporter, maintainer, separate, ignore / disregard / push, and go away from.